Accounting Quality in Eastern Europe after Communism - Frederick Lindahl; Hannu Schadéwitz (Taylor & Francis, 2022)
Research Question/Issue: This study, in the taxonomy of Schiehll and Martins (2016 Schiehll, E. and H. C. Martins. 2016. Cross-national governance research: A systematic review and assessment. Corporate Governance: An International Review 24 (3):181–99. doi:10.1111/corg.12158.[Crossref], [Web of Science ®], <a href="http://scholar.google.com/scholar_lookup?hl=en&publication_year=2016&pages=181-99&issue=3&author=E.+Schiehll&author=H.+C.+Martins&title=Cross-national+governance+research:+A+systematic+review+and+assessment&">[Google Scholar]), examines cross-national corporate governance, within their “legal” category. It rests on the understanding that to fully grasp corporate governance it is essential to understand the embedded institutions. The research question is: Does an increase in legal quality cause an associated increase in the quality of corporate governance in the form of financial reports to investors? If so, this supports the fundamental importance of legal systems to earnings quality. Reliable evidence on whether there is an association between legal quality and financial reporting quality would be an empirical association showing that where legal quality is higher, earnings quality is also higher, and conversely.
Research Findings/Insights: The results show clearly that in 2005 and 2010, when adequate data are available for testing, earnings quality is poor: far more companies show small gains than small losses. A great deal of managerial discretion is exercised in arriving at accounting figures, since many amounts depend on forecasts of future events. A significant number of firms use that latitude to show positive earnings. As to patterns of earnings management among three clusters of countries, the small number of firms generally precludes strong statistically supported evidence of management within the clusters. Nevertheless, the whole is the sum of the parts, and the parts (clusters) indicate the clusters most responsible for the overall result. There is little evidence of small gains exceeding small losses in the Baltics, greater differences in the Visegrád countries, and big differences in southern Europe.
Theoretical/Academic Implications: Based on both (a) the historical background of legal systems and (b) attitudes concerning legal quality measured at the same time as the earnings measures, the accounting results are consistent with the prediction of a strong legal culture driving effective corporate governance.
Practitioner/Policy Implications: The results show that eastern firms, on aggregate, have yet to reach the level of their western counterparts. However, the differences do not seem highly significant, and indicate that convergence is close in this area. This, in turn, should guide and encourage legislators in their work.